Analisis Nilai-Nilai Spiritual di KSPPS Khidmatul Ummah Bogor - Egi Agustian Rahmat Sukendar; Qurroh Ayuniyyah; Akhmad Affandi Mahfudz (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This research is about the Implementation of Spiritual KSPPS Khidmatul Ummah Bogor by using four variables as an analytical tool, namely sharia exemplary, sharia compliance, sharia education and sharia training. The Islamic economic discourse in the field of micro finance has not studied the implementation of Spiritual Intermediation in a holistic manner, even though the difference between Conventional Microfinance Institutions and Islamic Financial Institutions is the Spiritual and Social aspect. This analysis method uses a qualitative research style. The research approach is carried out in two stages, namely pilot research and pre-research. The results of this study are KSPSS Khidmatul Ummah Bogor institutionally is a sharia microfinance institution incorporated as a Sharia Savings and Loans Financing Cooperative Primary Scale District, which is engaged in empowering the poor and unbanked by carrying out social functions in Biatul Maal and business functions (tijari) through Baitul at Tamwil KSPSS Khidmatul Ummah. It is intended to be able to solve the economic problems of the lower middle class community in West Bogor, Bogor Regency. By implementing five pillars in its operations, namely: Alms, Savings, Soft Loans, Financing and Investment. And aspects of spiritual intermediation at KSPPS Khidmatul Ummah Bogor include: it is in accordance with Sharia principles and consistently exemplified by the administrators and managers. Sharia compliance has not been optimized properly. KSPSS Khidmatul Ummah Bogor in carrying out Sharia education and training to internal has been very intense, diverse and programmed. But for the external is not maximal, intense and diverse.